La actualización de la tradición de representación del paisaje y la flora de la Amazonía peruana en el siglo xxi - Giuliana Vidarte (Caravelle)
The landscape genre has been fundamental for the development of the pictorial tradition in the Peruvian Amazonia.  Furthermore, over the last few decades the most contemporary proposals have aimed to reinterpret and update this genre, as well as the images and  imaginations of the 19th and 20th century Amazonian archive. This article analyzes the consolidation of a regional artistic identity in Loreto based upon this genre, and reviews the way in which these works are updated in the 21st century in the pictorial proposals of Loreto artist Christian Bendayán.